Determinant of the Decision to Visit Tourist Attractions - Yessy Anggraeni; Suwignyo Widagdo; Yuniorita Indah Handayani (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
Tourism is one sector that can help the economy of a region. Tourism is also referred to as regional development credit. City branding is a form of effort made to form a place, an area which is then developed for the community. This study aims to determine the effect of city branding on visiting decisions either directly or through city image and electronic word of mouth. This research is a quantitative research, the subject of this research is tourists who visit tourist attractions in Lumajang who visit 139 people. Data collection using questionnaires and data analysis using path analysis. The results show that City branding affects the image of the city, city branding affects E-WOM, city image affects the decision to visit, E-WOM affects the decision to visit, city branding affects the decision to visit. City branding of a city can improve the image of the city with a brand created from existing tourism, branding of a city can increase promotion by means of E-Wom carried out by city visitors, the image of a good city can attract someone's decision to visit one of them with the image of natural tourism from one person to another.